HIV in the MENA Region - Mokhbat, Jacques E. (2016)
Over the last few years, our knowledge of the HIV epidemic and its drivers in the Middle East and North Africa (MENA) region have improved markedly, thanks to many recently conducted studies.1 While the annual number of new HIV infections in sub-Saharan Africa has declined by 33% since 2005, new HIV infections in the MENA region have increased by 31% since 2001, the greatest increase in all regions in the world. There are growing HIV epidemics in key populations (KPs) including people who inject drugs, men who have sex with men, and to a lesser extent, female sex workers.